The Effect of CMCE Propolis Extract Administrations on Interleukin-1 (IL-1) Levels and the Hepatocyte HistopathologicalFindings of Rats’ Induced with CCl4 - Lestari, Catur Retno; Sumarawati, Titiek; Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2020)
Introduction:Liver exposure to toxic substances will disrupt the metabolic system. Carbon tetrachloride (CCl4) is a hepatotoxic substance causing a liver damage. Continuous multi-stage countercurrent extraction(CMCE) propolis extract contains active balsamic substances, caffeic acid, phenethyl esters and flavonoids.Objective: to prove the effect of CMCE propolis extract on IL-1 levels and the hepatocyte histopathology findingsof male wistar rats’induced by CCl4.Methods:In the posttest only control group design, the total sample of 28 rats was divided into 4 groups: positive control group (K-0; standard feed); group P-1 (propolis3.6 mg/200 g); P-2 (propolis7.2mg/200gr and P-3 (propolis14.4mg/200g) were respectively given for 14 days,yet those on the 14thday were given CCl4. The IL-1 level was measured with the ELISA method, while the male wistar rats’hepatocyte histopathology findings was determined by the HE staining methods. IL-1 levelswere analyzed usingOne Way Anova test,followed by the Post Hoc LSD test. Hepatic cell histopathology was analyzed usingKruskal Wallis, followed by Mann-Whitney U.Results:Post Hoc LSD analysis shows that the levels of IL-1 in P-1 (983.54 ±19.67), P-2 (841.58±19.47), and P-3 (755.50±31.63) are significantlylower thanthosein K-0 (1131.69±14.91) withp<0.05. Mann-Whitney U analysis shows that the hepatocyte histopathology in the P-1 group (2.55±0.39), P-2 (1.24±0.94) and P-3 (1.20±0.93) is significantlylower thanthatinK-0 (2.94±0.16) with p<0.05.Conclusion: The administration of CMCE propolis extract may reduce IL-1 levels and improve the male wistar rats’hepatic cell histopathologyinduced with carbon tetrachloride (CCl4).